Trust Management in Times of Uncertainty and Risk - Wojciech PAWNIK (Communications of International Proceedings, 2021)
This paper offers the brief analysis of the role and importance of intra-organisational trust in Poland. The research problem concerns corporate trust management in a risk society during the Sars-Cov-2 pandemic. Pandemic times generate a loss of social ties and a growing lack of trust between individuals and groups. The level of social trust is reflected in organizational relationships. Critical analysis will be dealing with the functioning of organisation in risk society described by Urlich Beck. The so-called "future processes", i.e. increasing the effectiveness of economic activities, profitability of management and personnel reduction boil down to further subordination of the personnel model and strategies to the organisational strategies. The collection and analysis of information, the concentration on procedures, the search for efficiency criteria for social potential and organisational culture and the principle of maximising effects clearly indicate the continuation of the so-called modernist tradition in management proper to the classical school of management shaping an organisational order ensuring certainty and predictability of organisational behaviour. In managing the social potential of an organisation trust has been given the status of a "technical" reality. It is assumed that trust can be managed in the same way as the remaining resources of the organisation are managed. We then reify it instrumentally. However, the growing awareness of the employees about the role and importance of organisational scenarios and specific procedures marginalises the importance of intra-organisational trust. Due to the interdisciplinary nature of management science, the literature used relates to sociological, economic, and historical perspectives. One of the management sciences - sociology - answers three questions: how is it? Why is it so? How is it really? The author puts forward the thesis that the concept of trust management in an enterprise does not find its empirical justification in practical activities. The context of functioning of the organization - the time of the pandemic - also has no influence on the actual practices in this area. The so-called risk society co-creating the organization's environment is not a new quality in social and cultural terms.
Keywords: Social capacity management; uncertainty; trust; organisational procedures.